A new genus and species of flightless, microphthalmic Corythoderini (Coleoptera: Scarabaeidae: Aphodiinae) from Cambodia, associated with Macrotermes termites - Maruyama, Munetoshi (Zootaxa, 2012)
Eocorythoderus incredibilis, a new genus and new species, of Corythoderini is described. This new species was found infungus gardens of Macrotermes gilvus (Hagen, 1858) in Angkor Wat, Cambodia. The new taxon is a flightless, mi-crophthalmic species and the first corythoderine associated with Macrotermes Holmgren, 1910. The beetles were ob-served being carried by worker termites. Eocorythoderus is probably closely related to the genera Corythoderus Klug,1845 and Paracorythoderus Wasmann, 1918 (also Corythoderini). Some character states shared with the distantly-related termitophilous scarab genus Termitotrox Reichensperger, 1915 (Termitotrogini) are noted, and proposed as convergent.